2021
DOI: 10.3390/rs14010105
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for Combining Data Acquired by Unmanned Surface and Aerial Vehicles to Create Digital Bathymetric Models in Shallow and Ultra-Shallow Waters

Abstract: This paper presents a method for integrating data acquired by unmanned surface vehicles and unmanned aerial vehicles. The aim of this work was to create a uniform bathymetric surface extending to the shoreline. Such a body of water is usually characterized by ultra-shallow depths, which makes measurement impossible even with hydrographic autonomous vessels. Bathymetric data acquired by the photogrammetric method are, however, characterized by large errors with increasing depth. The presented method is based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 76 publications
1
21
0
Order By: Relevance
“…However, both ALB and MBES lack spectral information, limiting their further applications. The combination of ALB, MBES, and optical mapping sensors has been extensively researched and widely applied for inland water surveying [ 39 , 40 , 41 ] and coastal shallow water mapping [ 42 , 43 ]. Considering that the lightweight UAV-borne ALB system allows flexible installation, the integration of the system and optical cameras can be mounted on various UAV platforms.…”
Section: Discussionmentioning
confidence: 99%
“…However, both ALB and MBES lack spectral information, limiting their further applications. The combination of ALB, MBES, and optical mapping sensors has been extensively researched and widely applied for inland water surveying [ 39 , 40 , 41 ] and coastal shallow water mapping [ 42 , 43 ]. Considering that the lightweight UAV-borne ALB system allows flexible installation, the integration of the system and optical cameras can be mounted on various UAV platforms.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, based on different modifications of the IDW method, it was determined that the best results were obtained for 5-8 measurement points located within a radius of 0.6 m. Based on a study by Maleika [36], it should be concluded that the IDW method enables the modification of parameters, which translates into the method fitting to obtain the best results. The next example of the IDW application is presented in an article by Lubczonek et al [1]. It is noteworthy that the IDW method was applied to data derived from an UAV and an USV.…”
Section: Idwmentioning
confidence: 99%
“…Geodetic and hydrographic measurements are increasingly carried out by Unmanned Aerial Vehicles (UAV), Unmanned Surface Vehicles (USV) or Terrestrial Laser Scanners (TLS) [1][2][3]. The use of these modern methods in coastal zone measurements enables the acquisition of high-quality bathymetric data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A digital bathymetric model represents a topographic seafloor surface. It can be generated from bathymetric surveys with a Singlebeam or Multibeam Echosounder [13]. The periodic digital bathymetric model can be used to analyze the topographical change in specific time intervals by calculating volume [14].…”
Section: Introductionmentioning
confidence: 99%